Study of single dose test of Sweet Bee Venom in rats - Young Jin Kim; Chung San Lim; Ki Rok, Kwon (Journal of Pharmacopuncture, 2009)
Objectives: This study was performed to analyse single dose toxicity of pure melittin(Sweet Bee Venom-Sweet BV) extracted from the bee venom by utilizing protein isolation method of gel filtration. Methods: All experiments were conducted at Biotoxtech, a non-clinical studies authorized institution, under the regulations of Good Laboratory Practice (GLP). Six weeks old female Sprague-Dawley rats were chosen for the pilot study and determined 30㎎/㎏ which is 4285 times higher than the clinical application dosage as the high dosage, followed by 15 and 7.5㎎/㎏ as mid and lose dosage, respectively. Equal amount of excipient to the Sweet BV experiment groups was administered as the control group. Results: 1. No mortality was witnessed in all of the experiment groups. 2. Hyperemia and movement disorder were observed around the area of administration in all groups, and higher occurrence in the higher dosage groups. Hyperemia and movement disorder diminished with elapsed time. 3. For the weight measurement, male groups showed larger reduction in weight in accordance with higher dosage. Female groups didn't s how significant changes. 4. To verify abnormalities of organs and tissues, cerebellum, cerebrum, liver, lung, kidney, and spinal nerves were removed and conducted histological observation with H-E staining. No abnormalities were detected in any of organs and tissues. 5. One female rat in the 30㎎/㎏ group had amputated toe near the administered area and histopathological finding was hemorrhage with inflammation. This is presumed as a secondary infection after the administration of Sweet BV. Conclusion: Above findings suggest Sweet BV is relatively s safe treatment medium. Further studies on the subject should be conducted to yield more concrete evidences.